Decoding the pathological and genomic profile of epithelial ovarian cancer - Rim Rejaibi; Arnaud Guille; Maroua Manai; Jose Adelaide; Emilie Agavnian; Aida Jelassi; Raoudha Doghri; Emmanuelle Charafe-Jauffret; François Bertucci; Mohamed Manai; Karima Mrad; Lamia Charfi; et al. (Scientific Reports)
Abstract Ovarian cancer (OC) is one of the most common cancers in women, with a high mortality rate. Most of published studies have been focused on Caucasian populations, with the need to explore biological features and clinical outcomes of patients from other ethnicities. We described clinical outcome (progression-free survival and overall survival) and biomarkers associated with survival in a cohort of patients with OC from Tunisia. Using immunohistochemistry, we assessed the expression of 14 proteins known to be altered in OC in a cohort of 198 patients. We explored the correlation between protein expression and copy number alteration (CNA) profiles. FIGO stage, menopausal status and mismatch repair deficiency were associated with survival. ERBB2 amplification was correlated with high ERBB2 expression (OR = 69.32, p = 4.03 E-09), and high PDL1 expression was associated to CD274 amplification (OR = 4.97, p = 5.79 E-2). We identified a correlation between survival and exposure to two CNA signatures (MAPK pathway and BRCA-related homologous recombination deficiency). Moreover, Gama-H2AX protein expression was correlated with exposure to a genomic signature associated with homologous recombination deficiency. We observed that OC clinical and pathological characteristics of these patients from Tunisia were similar to those of Caucasian patients. We identified frequent CNA in this population that need to be confirmed in other sets from Africa.